The Readiness of Islamic Banking in Indonesia to Implement Digital and Green Banking - Malik Cahyadin; Tamat Sarmidi; Elsa Adelia Nurrachma (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2019)
This study aims to analyze: (a) the relationship between Islamic banking asset and financing, ICT Index, and Environmental quality index in Indonesia; and (b) the readiness level of Islamic banking in Indonesia to implement digital and green banking. The data used are asset growth, financing growth, IDI and IKLH. Period of data used is annual from 2010-2016. Methods of data analysis include descriptive statistics, correlation and Granger causality test. The results show that: (a) asset and financing of Islamic Banking have correlation/causality with IDI and IKLH; and (b) the readiness level of digital banking is 3 while the readiness level of green banking is 1. Islamic banking in Indonesia has utilized ICT in asset management and financing. Meanwhile, Islamic banking has not been able to play an active role in controlling the environmental impact of financial transactions. The recommendation of this research is OJK should set periodization of digital and green banking implementation in Islamic banking supported by DSN-MUI fatwa. OJK could also establish the index of digital and green banking in Indonesia Islamic banking.